Insulating Materials Conduction After Ions Irradiation and Annealing; 12th International Conference on Surface Modification of Materials by Ion Beams, Marburg, Germany, September 9-14, 2001 : abstracts - Kabyshev A. V. Alexander Vasilievich; Konusov F. V. Fedor Valerievich; Kurakov A. G. Andrey Grigorievich; Lopatin V. V. Vladimir Vasilyevich (2001, 2001)
В фонде НТБ ТПУ отсутствует